Interband cascade lasers. (11th March 2015) - Vurgaftman, I; Weih, R; Kamp, M; Meyer, J R; Canedy, C L; Kim, C S; Kim, M; Bewley, W W; Merritt, C D; Abell, J; Höfling, S
Abstract: We review the current status of interband cascade lasers (ICLs) emitting in the midwave infrared (IR). The ICL may be considered the hybrid of a conventional diode laser that generates photons via electron–hole recombination, and an intersubband-based quantum cascade laser (QCL) that stacks multiple stages for enhanced current efficiency. Following a brief historical overview, we discuss theoretical aspects of the active region and core designs, growth by molecular beam epitaxy, and the processing of broad-area, narrow-ridge, and distributed feedback (DFB) devices. We then review the experimental performance of pulsed broad area ICLs, as well as the continuous-wave (cw) characteristics of narrow ridges having good beam quality and DFBs producing output in a single spectral mode. Because the threshold drive powers are far lower than those of QCLs throughout the λ = 3–6  µ m spectral band, ICLs are increasingly viewed as the laser of choice for mid-IR laser spectroscopy applications that do not require high output power but need to be hand-portable and/or battery operated. Demonstrated ICL performance characteristics to date include threshold current densities as low as 106 A cm −2 at room temperature (RT), cw threshold drive powers as low as 29 mW at RT, maximum cw operating temperatures as high as 118 °C, maximum cw output powers exceeding 400 mW at RT, maximum cw wallplug efficiencies as high as 18% at RT, maximum cw single-mode output powers as high as 55 mW at RT, and single-mode output at λ = 5.2  µ m with a cw drive power of only 138 mW at RT.